"Walk Cheerfully Over the Earth": A Spiritual Profile of Senator Tim Kaine. (January 2019) - McCloskey, Liz
The following is excerpted from Senator Tim Kaine's spiritual profile, part of a larger project in collaboration with Senator Chris Coons titled Profiles in Spirit that provides glimpses of the spiritual lives of selected political leaders. In an effort to push back against the relentless negativity that poisons national politics, these profiles focus on the humanity and spiritual depth of individuals who hold public office by tracing spiritual themes threaded through their lives.